The Association between Abnormal Vaginal Flora and Cytological Evidence of HPV with Prematurity in High-Risk Pregnant Women - Freire, Alana Dantas; Custódio, Ada Isa; Filho, José Queiroz; Freitas, Janaína Crispim; Gonçalves, Ana Katherine; Cobucci, Ricardo Ney (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: To evaluate the association between abnormal vaginal flora and cytological evidence of HPV with prematurity in high-risk pregnant women. Study design: A prospective cohort study was designed with high-risk pregnant women who delivered singletons between 20-42 gestational weeks between January to November 2018. Vaginal specimens were collected to obtain material from the upper lateral vaginal vault and cervix for direct microscopic examination of vaginal contents and preparation of Gram-stained and pap smear slides. Potential determinants of infection were assessed using the chi-square test. Poisson regression was used to determine the prevalence ratio and 95% confidence interval of the association between the vaginal flora and cytology with prematurity and a p <0.05 was considered as statistical significance. Results: A total of 68 pap smear and high vaginal swab samples were collected from high-risk pregnant women with a mean age of 30.3 years. There were 26 (38.2%) cases of abnormal vaginal flora and 6 (8.8%) of HPV-induced cytological abnormalities. The preterm delivery rate was comparable between women with normal and abnormal vaginal flora (11.9% vs. 11.5%, prevalence ratio 1.0 [95% confidence interval: 0.8-1.2], aPR 1.0 [95% confidence interval: 0.8-1.2]) and between women with and without abnormal cytology (16.7% vs. 11.3%, prevalence ratio 0.9 [95% confidence interval: 0.6-1.4], aPR 0.9 [95% confidence interval: 0.6-1.4]). Conclusions: We determined no association between abnormal cytology or altered vaginal flora in high-risk pregnancy in terms of overall preterm birth rate.